Efek Antihiperkolesterolemia Ekstrak Buah Belimbing Wuluh (Averrhoa bilimbi Linn.) terhadap Kadar Kolesterol LDL Tikus Putih (Rattus norvegicus) - Rosmalianti, Andina (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2012)
Background: Current lifestyle has shifted towards high fat diet which leads to hypercholesterolemia. The increased LDL cholesterol (LDL-C) level is a risk factor for coronary heart disease. Natural plants have been increasingly used to manage metabolic diseases such as hypercholesterolemia. Among the plants is bilimbi fruit which is assumed to have anticholesterol effect owing to its bioactive components, namely pectin, saponin, and niacin. This research aims to examine the effect of bilimbi fruit extract on LDL-C levels in cholesterol-fed white rats. Methods: This was an experimental study using post test only controlled group design. A total of 35 white male Wistar rats aged 2-3 months and weighed 160-200 grams were assigned into five groups, i.e. normal control group, positive control group, negative control group, and two treatment groups with bilimbi fruit extract at dosage I and II. After being adapted for a week, all groups but normal control, were given hypercholes-terolemic food and 0,01% PTU for 14 days. At day 22, positive control group was given simvastatin 0,8 mg/200 gBW, and treatment groups were given bilimbi fruit extract at dosages of 40 mg/200 gBW and 80 mg/200 g BW, respectively for 14 days. Blood samples were taken through retro-orbital venous at day 37 to measure LDL-C levels. Data were analyzed using one way ANOVA test followed by LSD test. Results: Mean LDL-C levels differed significantly across groups (p<0,001). Results from LSD tests showed significant differences between positive control group as well as treatment groups at dosage I and II compared to negative control group (p<0,01). There were significant diferences of mean LDL-C levels between positive control group (p=0,044) and normal control group (p=0,001) compared to bilimbi fruit extract group at dosage I. No LDL-C level differences were found between bilimbi fruit extract at dosage II compared to positive control group (p=0,246) and to normal control group (p=0,790). Conclusions: Bilimbi fruit extract at dosage 40 mg/200 gBW and 80 mg/200gBW significantly decreased LDL-C levels in hypercholesterolemic white rats. Keywords: Bilimbi fruit extract, LDL-C, hypercholesterolemia